Comparing the immediate effects of a total motion release warm-up and a dynamic warm-up protocol on the dominant shoulder in baseball athletes - Gamma, S. C.; Baker, R.; May, J.; Seegmiller, J. G.; Nasypany, A.; Iorio, S. M. (The Journal of Strength and Conditioning Research, 2020)
A decrease in total range of motion (ROM) of the dominant shoulder may predispose baseball athletes to increased shoulder injury risk; the most effective technique for improving ROM is unknown. The purpose of this study was to compare the immediate effects of Total Motion Release (TMR) to a generic dynamic warm-up program in baseball athletes. Baseball athletes (n = 20) were randomly assigned to an intervention group: TMR group (TMRG; n = 10) or traditional warm-up group (TWG; n = 10). Shoulder ROM measurements were recorded for internal rotation (IR) and external rotation (ER), the intervention was applied, and postmeasurements were recorded. Each group then received the other intervention and postmeasurements were again recorded. The time main effect (p = 0.001) and the time × group interaction effect were significant (p = 0.001) for IR and ER. Post hoc analysis revealed that TMR produced significant increases in mean IR (p = 0.005, d = 1.52) and ER (p = 0.018, d = 1.22) of the dominant shoulder initially. When groups crossed-over, the TMRG experienced a decrease in mean IR and ER after the dynamic warm-up, whereas the TWG experienced a significant increase in mean IR (p = 0.001, d = 3.08) and ER (p = 0.001, d = 2.56) after TMR intervention. Total Motion Release increased IR and ER of the dominant shoulder more than a dynamic warm-up. Dynamic warm-up after TMR also resulted in decreased IR and ER; however, TMR after dynamic warm-up significantly improved IR and ER. Based on these results, TMR is more effective than a generic dynamic warm-up for improving dominant shoulder ROM in baseball players.